Development Of A Community-Based Sports Tourism Village And Local Wisdom Product As A Basis For Competitive Advantage In Cijagamulya Village, Kuningan Regency - Gana Wuntu; Mengku Marhendi (International Conference On Digital Advanced Tourism Management And Technology, 2023)
Every village that is pioneered as a tourist destination should be unique so that it can compete with other tourist villages. This research aims to identify the potential for sports tourism in Cijagamulya village, identify local wisdom products that can support the development of sports tourism, and to formulate a community empowerment strategy within the framework of the Cijagamultya development model as a community-based sports tourism village to provide economic impacts on its community. The research was conducted with a qualitative method, conducting in-depth interviews with a number of informants. The results showed that Cijagamulya village has the potential for sports tourism, has facilities and various alternative types of sports. Various MSMEs are ready to develop local wisdom products in supporting the pioneering of Cijagamulya village as a competitive tourist village. This research also proposes a framework for the development of a community-based sports tourism village.